2013
DOI: 10.5897/ajar11.1533
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Arsi-Bale kids supplemented with graded levels of pigeonpea in dry season in Mid Rift valley of Ethiopia

Abstract: Free grazing/browsing Arsi-Bale kids in dry season were supplemented with different levels of dried pigeon pea (Cajanus cajun) leaves to study its effect on weight gain. Kids browsed freely (PP 0 ), and/or supplemented with 66 g (PP 66 ), 99 g (PP 99 ) and 132 g (PP 132 PP) of sun dried pigeon pea leaves. Supplementation significantly (P<0.05) increased average daily gain of kids but there was no significant (P<0.05) difference between kids supplemented with PP 99 and PP 132 g in terms of total weight gain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…microbial functions(Van Soest, 1994). The CP contents of IFTSs obtained in this study are within the range of earlier studies(Belete et al, 2012;Andualem et al, 2015), which reported CP values ranging between 8.9% and 20.9% DM for indigenous browse species. Intake declines sharply when forage contains < 7% CP(McDonald et al, 2010).…”
supporting
confidence: 88%
“…microbial functions(Van Soest, 1994). The CP contents of IFTSs obtained in this study are within the range of earlier studies(Belete et al, 2012;Andualem et al, 2015), which reported CP values ranging between 8.9% and 20.9% DM for indigenous browse species. Intake declines sharply when forage contains < 7% CP(McDonald et al, 2010).…”
supporting
confidence: 88%
“…It improves soil fertility and benefits cereal crops through nitrogen fixation when they are intercropped or used in crop rotation [2]. It is also used as fodder for domestic animals and enhances ruminant live weight due to its relatively higher nitrogen concentration [3]. It is capable of providing some grain yields for the period of dry spells when other legumes such as field beans have wilted and possibly dried up as a result of its deep rooted and drought-tolerant nature [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cajanus cajan L. est une légumineuse arbustive fourragère et vivrière qui s'intègre bien en Afrique dans les systèmes de production culture-bétail (Onana et al, 2007 ;Pal et al, 2011). Elle produit une grande quantité de biomasse fourragère de haute qualité (Fondevila et al, 2002 ;Shenkute et al, 2013) et est également utilisée dans le traitement de certaines pathologies humaines et animales (Pal et al, 2011;Ogni et al, 2014;N'draman-donou et al, 2015). Sur le plan parasitaire, l'action de Cajanus cajan contre les nématodes gastro-intestinaux (Pal et al, 2011;Kaboré et al, 2016) est à ce jour documentée.…”
Section: Introductionunclassified